2014
DOI: 10.1121/1.4861839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of impedance phase angle on sound pressures and reverberation times in a rectangular room

Abstract: In most room acoustic predictions, phase shift on reflection has been overlooked. This study aims to quantify the effects of the surface impedance phase angle of the boundary surfaces on room acoustic conditions. As a preliminary attempt, a medium-sized rectangular room is simulated by a phased beam tracing model, after verifying it numerically against boundary element simulations. First, the absorption characteristic of the boundary surfaces varies uniformly from 0.2 to 0.8, but with various impedance phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…In the area of beam tracing method, some recent works [31][32][33] focused on the influence of boundary conditions on the prediction results. In the work of Siltanen et al [ 34], they presented a way to introduce incoherent reflections in a beam tracer algorithm.…”
Section: Geometrical Acoustical Methodsmentioning
confidence: 99%
“…In the area of beam tracing method, some recent works [31][32][33] focused on the influence of boundary conditions on the prediction results. In the work of Siltanen et al [ 34], they presented a way to introduce incoherent reflections in a beam tracer algorithm.…”
Section: Geometrical Acoustical Methodsmentioning
confidence: 99%
“…In either case, these differences may be audible to some listeners, since the just-noticeable-difference for broadband signals is 0.5-1 dB. 24,25 It is interesting to note that the correlation between error and SPL is present at other frequencies as well, particularly at 33, 51, 68, 86, and 103 Hz for model 1. The higher error is less pronounced for model 4 ( 0 < 0.5 dB from 20 to 100 Hz).…”
Section: A Spl and Accuracymentioning
confidence: 98%
“…Jeong (2012) investigated real and complex-valued boundary conditions using the phased beam tracing method and found that the impedance phase angle affects the sound pressure level. In the study of Jeong et al (2014), the phased beam tracing method was used to investigate the perceived reverberance for the wall impedance with different phase angles. It was found that, for uniform absorption settings, the non-zero impedance phase angle results in a perceptual difference in reverberance when compared to a zero-phase impedance.…”
Section: Introductionmentioning
confidence: 99%